A community based study to assess the validity of Indian diabetic risk score, among urban population of North Central India - Agarwal, Anil Kumar; Ahirwar, Ghanshyam; Marskole, Priyesh; Bhagwat, A. K. (International Journal Of Community Medicine And Public Health, 2017)
Background: The prevalence of diabetes mellitus is growing rapidly worldwide and India has earned the dubious distinction of being the diabetic capital of the world and had 69.2 million (8.7%) people living with diabetes.1 Unfortunately over half of these people remain undiagnosed as diabetes. IDRS is a cost effective and simple tool for screening of undiagnosed diabetic individuals in the community. The objective of the study was to estimate prevalence of undiagnosed high risk subjects of diabetes mellitus to validate IDRS as effective tool for diagnosis of diabetes in urban areas of Gwalior City. Methods: In community based cross-sectional observational study house to house survey was conducted and face to face interview had done by predesigned questionnaire, which was based on IDRS variables for those persons of age more than 20 and not known to diabetes previously. Results: In present study 55 (8.94%) out of 615 respondents were diagnosed as a newly diabetic cases. We found that at IDRS score of ≥60 has a sensitivity of 45.5% and specificity of 88.0%. Conclusions: This study provides a use of Indian diabetes risk score for identifying undiagnosed high risk for patients with diabetes in Indian population and could make screening programmes more cost effective.